Generic Checkpointing Support for Stream-based State-Machine Replication - Lawniczak, Laura; Ammon, Marco; Distler, Tobias (Proceedings of the 10th Workshop on Principles and Practice of Consistency for Distributed Data (PaPoC '23), 2023)
Stream-based replication facilitates the deployment and operation of state-machine replication protocols by running them as applications on top of data-stream processing frameworks. Taking advantage of platform-provided features, this approach makes it possible to significantly minimize implementation complexity at the protocol level. To further extend the associated benefits, in this paper we examine how the concept can be used to provide generic support for creating, storing, and applying checkpoints of replica states, both in the use case for catch up and garbage collection as well as to recover failed replicas. Specifically, we present three checkpointing-mechanism designs with different degrees of platform involvement and evaluate them in the context of Twitter's stream-processing engine Heron.<br
Keywords: State-machine replication; checkpointing; recovery; data-stream processing

Micro Replication - Distler, Tobias; Eischer, Michael; Lawniczak, Laura (Proceedings of the 53rd Annual IEEE/IFIP International Conference on Dependable Systems and Networks (DSN '23), 2023)
State-machine replication protocols represent the foundation of many fault-tolerant services. Unfortunately, their inherent complexity makes existing implementations notoriously difficult to debug and test. To address this problem, we propose a novel design approach, micro replication, whose main goal is to reduce bugs and enable replication protocols with improved debuggability properties. At its core, our concept consists of a set of principles that, if followed during protocol design, later significantly facilitate crucial tasks such as bug-source isolation, state-information retrieval, as well as root-cause identification. To achieve this, micro replication organizes a protocol as a composition of specialized modules ('micro replicas') that each encapsulate a particular protocol phase or mechanism, and therefore are easier to test and monitor than traditional monolithic replicas. Besides discussing the underlying ideas of our approach, to show its feasibility we also present and evaluate Mirador, the first micro-replicated Byzantine fault-tolerant protocol.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Debuggability; Fault Tolerance; Replication

Stream-based State Machine Replication - Lawniczak, Laura; Distler, Tobias (Proceedings of the 17th European Dependable Computing Conference (EDCC '21), 2021)

Targeting Tail Latency in Replicated Systems with Proactive Rejection - Lawniczak, Laura; Distler, Tobias (Proceedings of the 25th Middleware Conference (Middleware '24), 2024)

Tough on the Outside, Reliable on the Inside: Utilizing System Composition for Improved Resilience - Lawniczak, Laura; Distler, Tobias (1st Workshop on Resilient Operations – Byzantine Fault Tolerance and State-Machine Replication (ROBUST '24), 2024)
The notoriously high complexity of Byzantine fault-tolerant (BFT) protocols leads to a high risk of bugs and vulnerabilities and makes diversification costly. We aim to increase the resilience of BFT systems by introducing a new hybrid fault model focussing on the composition of the system. ShellFT structures a BFT system into two main parts: 1. A BFT shell that handles client interaction and is connected to the outside world, and 2. a crash fault-tolerant core providing the protocol logic that is only connected to other replicas. With this approach, we aim to significantly reduce the code base of the BFT parts, making it easier to find vulnerabilities and use diversification. Exploiting the intrinsic modularization of the design paradigm micro replication, we devise a ShellFT variant of the Mirador protocol.<br